Applying the Tier II Construction Management Strategy to Measure the Competency Level among Single and Multiskilled Craft Professionals - Albalawi, Rakan K.; Goodrum, Paul M.; Taylor, Timothy R. B. (Buildings (Basel), 2023)
Various contemporary studies have revealed a heightened need for the implementation of effective strategies to reduce labor shortages in the construction industry. The subsequent investigation outcomes have identified multiskilling labor strategies as viable solutions to alleviate labor deficiencies in the construction sector. These strategies aim to train single-skilled craft professionals so that they can acquire different skills and complete tasks in addition to their primary duties in the workplace; however, limitations exist in terms of measuring competency levels among single-skilled and multiskilled craft professionals. Thus, a workforce management strategy, referred to as Tier II strategy metrics, is used in this study as a comprehensive approach to evaluate the construction workers’ competency levels among more than 2740 workers in the industry. Furthermore, multinomial logistic regression was applied to explain the variability in both the project craft technical and project craft management Tier II score. The overall average Tier II score for multiskilled workers was 6.27, whereas single-skilled workers scored 5.17. The results show that multiskilled craft professionals have higher competency levels compared with single-skilled craft professionals. The outcome from the regression model demonstrates that craft workers who are experts and multiskilled are competent in terms of their project craft technical skill, and years of experience is the most important variable for predicting high competency levels.